Perspektif guru terhadap implementasi model kooperatif tipe tgt dalam keterampilan kolaborasi siswa di SDIT Laa Tahzan Citra - Arrasuli, Balqis Azzahra; Hapudin, Muhammad Soleh (Jurnal Pendidikan Dasar, 2000)
This study aims to explore teachers perspectives on the implementation of the cooperative learning model, Teams Games Tournament (TGT), as part of students' collaborative skills learning at SDIT Laa Tahzan Citra. This research employs a qualitative approach with a narrative method, and data is collected through indepth interviews with fifth and sixth-grade teachers who have implemented the TGT model. The study focuses on teachers' understanding of TGT, the strategies applied, the challenges encountered, and its impact on students' collaborative skills. The findings reveal that teachers' understanding of this model varies, influenced by their experience and available sources of information. In practice, teachers employ strategies such as heterogeneous group formation, assigning roles based on students' abilities, providing guidance during tournaments, and implementing rewards and punishments. Challenges include limited resources, differences in students' academic abilities, time management, group interactions, and variations in students' learning motivation. Nevertheless, the TGT model positively impacts students' collaborative skills, particularly in social interactions, teamwork, and emotional management while participating in group activities.